My Cigarette Wife and Other Queer Tales of Kinship from Tunisia’s Contemporary Public Art Scene - Malachowski, Justin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This article explores the contradictions and political possibilities of creating a “safe space” using “family” as an organizational concept in a contemporary public art project in Tunisia. Amidst the backdrop of foreign development funding for the arts flowing into Tunisia and a global contemporary art scene where “patriarchal structures” are taken as antithetical to collaborative practices, family has been an intuitive and meaningful mode of organizing artistic projects in Tunisia, particularly as it relates to fostering safe spaces for queer youth. As opposed to “participation,” “commoning,” and other institutionally supported art concepts, family is not a concept widely exhibited. In relation to tendencies toward “sensible” approaches to the political efficacy of contemporary art, the artistic practice of making family points to a “nonsensible” politics of aesthetics, where the aesthetic is better understood not as the location of politics but as a quality of feeling that enables spaces of political possibility.
Keywords: Art; Tunisia; Queer; Family; Politics of Aesthetics